CAN MARKET POTENTIAL EXPLAIN REGIONAL DISPARITIES IN DEVELOPING COUNTRIES? EVIDENCE FROM TURKEY - DOĞRUEL, FATMA (WILEY, 2016)
Regional disparity is one of the important characteristics of the Turkish economy. This study examines the impact of market potential on the regional differences in Turkey by investigating wages in the manufacturing industry for 1987 and 2000. Evidence suggests that market potential is an important determinant of inequality in Turkey. In addition, public-private decomposition reshapes the dispersion of wages supportive of rising heterogeneity in the private manufacturing industry. This increases the explanatory power of market potential, which is observed to be high in western Turkey and diminishes toward eastern Turkey. Our findings highlight that during the postliberalization era of the 1980s, Turkey's regional inequality concern transformed into a structural problem which can be explained by provincial market potential. Moreover, our results underline that the modern geography framework, which has been tested for developed economies, is able to elucidate the regional differences in a developing country suffering from persistent imbalances.
Keywords: Market potential; Regional disparities; Wage equation; Turkey; ECONOMIC-GEOGRAPHY; TRADE; WAGE